Influence of drayage patterns on truck appointment systems - Ann-Kathrin Lange; Kristof Ole Kühl; Anne Kathrina Schwientek; Carlos Jahn (Logistics 4.0 and Sustainable Supply Chain Management: Innovative Solutions for Logistics and Sustainable Supply Chain Management in the Context of Industry 4.0. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 26, 2018)
Truck appointment systems (TAS) are a well-recognized method to smooth the peaks in truck arrivals at seaport container terminals and thereby reduce operation costs for the terminals and waiting times for trucking companies. This study analyzes the influence of different drayage patterns on the success of a TAS at seaport container terminals by means of a discrete event simulation model. These drayage patterns vary in the percentages of transports between container terminals and container terminals and other logistics nodes. Past studies mainly focus on the general impact of TAS on container terminals or on trucking companies. Rarely different TAS' characteristics are analyzed regarding their impact on the performance. To the authors' knowledge, the influence of varying shares of different drayage origins and destinations have not been studied so far. The results show that the pattern of drayage transports has a considerable influence on the success of TAS. As the transport from terminals to logistics nodes and vice versa is bound to the opening hours of the logistics nodes, trucking companies often need to execute inter terminal transports at night.
urn:nbn:de:gbv:830-88223600; 10419/209195; https://econpapers.repec.org/RePEc:zbw:hiclpr:26
Keywords: 650; Truck Appointment System; Port Drayage; Container terminal; Simulation